PENGARUH MODEL PEMBELAJARAN CONNECTED MATHEMATICS PROJECT (CMP) BERBANTUAN GOOGLE SITE TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS - Nur Layaliya Buraidah; Fadhilah Rahmawati (LPPM Universitas Bina Bangsa, 2023)
The purpose of this study was to analyze the ability to understand mathematical concepts of students who were taught with the Google Site-assisted CMP learning model better than those taught with the direct learning model. The next objective is to analyze the ability to improve understanding of mathematical concepts taught with the Google Site-assisted CMP learning model for derived material. This research is quantitative research with quasi-experimental design. The nonequivalent control group design was used as a form of quasi-experimental, by comparing two samples of 44 students from class XI MIPA SMA Negeri 2 Magelang who were randomly selected. From the Independent Sample t-Test test it produces a value of then is rejected and is accepted which means the ability to understand mathematical concepts taught with the Google Site-assisted CMP learning model is better than the direct learning model. Then, the average N-Gain test was 0.38 and proved that there was an increase taught by the Google Site-assisted CMP learning model for derivative material in the medium category. From the results of hypothesis testing, it can be concluded that the ability to understand mathematical concepts taught by the Google Site-assisted CMP learning model is better than the direct learning model for derivative material, and there is an increase in the moderate category.